F20 Evaluating body mass composition in huntington's disease by dexa. (16th November 2010) - Salvatore, E; Tucci, T; Rinaldi, C; Russo, C V; Rossi, F; Di Maio, L; Colao, A; Porcaro, F; Filla, A; Mainolfi, C; De Michele, G
Abstract : Background: Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder, caused by an increased CAG repeat size in the huntingtin gene. Apart from motor, cognitive, and psychiatric signs, other features, as dysautonomia, weight loss, sleep disturbances, and neuroendocrine disturbances may affect quality of life. Decreased bone density was shown in HD mice and in patients, according to preliminary reports. Aims: Aim of this study was to evaluate bone mineral density (BMD) and whole mass body distribution by DEXA in HD patients and to correlate them to clinical and endocrine data. Patients & methods: We investigated 14 consecutive patients seen at our HD Clinics. Clinical assessment of patients was performed using the Unified Huntington's Disease Rating Scale (UHDRS) motor section and the Total Function Capacity (TFC). Wide basal metabolic and endocrine investigations included serum calcium, phosphorus, alkaline phosphatase, cortisol, FSH, LH, estradiol, testosterone, androstenedione, DHEAS, insulin, growth hormone, insulin-like growth factor 1 (IGF-1). Patients and underwent dual-energy X-ray absorptiometry (DEXA) at the lumbar spine and femoral neck. Individual BMD, lean, fat and total mass values were expressed as g/cm2 and T- and Z-scores. Osteopenia and osteoporosis were diagnosed according to World Health Organization (WHO) criteria. Results: Abnormal bone mineral density was present in 3/14 (21%) of patients with HD. Two patients had osteopenia and one had osteoporosis. CAG size was negative correlated with body mass index (r=−0.959, p<0.01), cortisol (r=−0.917, p<0.05), and fat mass (r=−0.999, p<0.01). Conclusions: Our data, in line with data from preliminary report, show that osteoporosis may be part also of the HD phenotype, even in early disease stages. BMD values did not show any correlation with expected parameters like cortisol. Further investigations are needed to confirm this and to clarify if decreased bone mineral density could be due to a direct effect of mutant huntingtin on osteoblasts or osteoclasts in bone tissue.